On-farm pig dispatch methods employed in Brazil and stockpeople attitudes on their use - Dalla Costa, F A; Gibson, T J; Octavio Oliveira, S E; Gregory, N G; Coldebella, A; Faucitano, L; Dalla Costa, O A (Livestock Science, 2019)
This study surveyed the on-farm dispatching methods used at pig farms, the characteristics of stockpeople operating them, in terms of training and management, and their opinions and attitudes about the efficiency and safety of the applied procedures. Independently of the pig type, the most used dispatching methods at the surveyed Brazilian farms were concussion (90%) and electrocution (5%). Both methods were reported as being efficient and safe for on-farm pig dispatching by most stockpeople (83%). However, 33% of all stockpeople reported they would prefer to use alternative methods, i.e., anesthetics (23%) or electrocution (32%). Only 7% of the stockpeople received training resulting in a more efficient application of the method (P
Keywords: ePrints migration